FAKTOR-FAKTOR YANG MEMPENGARUHI STATUS GIZI BALITA DI PUSKESMAS KRUI KABUPATEN PESISIR BARAT - Angga Herlambang; Riska Wandini; Setiawati Setiawati (Program Studi Kebidanan Fakultas Kedokteran Universitas Malahayati, 2021)
Introduction: Toddler nutrition problems are still a global problem. The number of malnourished children in developing countries reaches 181.92 million (32%). Data in Indonesia in 2018 the percentage of malnutrition is 3.9%, while malnutrition is 13.8%. In Lampung Province in 2018, 3.1% of children under five experienced malnutrition, and 12.8% for undernutrition. This figure according to WHO has been considered a health problem because its prevalence is> 15.0%. Data of West Pesisir Regency in 2018, the percentage of malnutrition and malnutrition in children aged 0-59 months is 2.06% for malnutrition, and 9.01 for malnutrition.Purpose: To identify the factors that influence the nutritional status of children under five.Method: This type of research is quantitative with cross sectional approach. The population was all mothers and children under five in the Krui Public Health Center in West Pesisir Regency, with a total sample of 268 people, using proportional random sampling. Data analysis in this study used the chi-square test.Results: The results of univariate analysis showed that most respondents were well-informed (74.6%), had good birth spacing, as many as 171 people (63.8%), had good socio-economic conditions, as many as 155 people (57.8%) . The results of the bivariate analysis that there is a relationship of knowledge (p-value = 0.000, and OR = 7.846), birth spacing (p-value = 0.000, and OR = 7.304), and socioeconomic with the nutritional status of children under five in Krui Public Health Center West Pesisir Regency 2020 (p-value = 0.000, and OR = 2.575).Conclusion: there is a relationship of knowledge, birth spacing, socioeconomic, with the nutritional status of children under five in the Krui Public Health Center, West Pesisir Regency. Suggestions for improving counseling and also risk factors such as birth spacing that is too tight. Keywords: Factors, Malnutrition, Under Five Years Old Pendahuluan: Masalah gizi balita masih menjadi permasalahan global. Jumlah anak kekurangan gizi di negara yang berkembang mencapai 181,92 juta (32%). Data di Indonesia tahun 2018 persentase gizi buruk yaitu 3,9%, sedangkan gizi kurang yatu 13,8%. Di Provinsi Lampung tahun 2018 sebanyak 3,1% balita mengalami gizi buruk, dan 12,8% untuk gizi kurang. Angka ini menurut WHO sudah dianggap masalah kesehatan karena prevalensinya >15,0%. Data Kabupaten Pesisir Barat tahun 2018, persentase gizi buruk dan gizi kurang pada balita usia 0-59 bulan yaitu sebesar 2,06% untuk gizi buruk, dan 9,01 untuk gizi kurang.Tujuan: Diketahui faktor-faktor yang mempengaruhi status gizi balita.Metode: Jenis penelitian adalah kuantitatif dengan pendekatan cross sectional. Populasi adalah seluruh ibu berserta balita di Puskesmas Krui Kabupaten Pesisir Barat, dengan jumlah sampel 268 orang, menggunakan proportional random sampling. Analisis data pada penelitian ini menggunakan uji chi-square.Hasil Penelitian: Hasil analisis univariat bahwa sebagian besar responden berpengetahuan baik (74,6%), memiliki jarak kelahiran baik, yaitu sebanyak 171 orang (63,8%), memiliki sosial ekonomi baik, yaitu sebanyak 155 orang (57,8%). Hasil analisis bivariat bahwa ada hubungan pengetahuan (p-value = 0.000, dan OR= 7.846), jarak kelahiran (p-value = 0.000, dan OR= 7.304), dan sosial ekonomi dengan status gizi balita di Puskesmas Krui Kabupaten Pesisir Barat Tahun 2020 (p-value = 0.000, dan OR= 2.575).Kesimpulan: ada hubungan pengetahuan, jarak kelahiran, sosial ekonomi, dengan dengan status gizi balita di Puskesmas Krui Kabupaten Pesisir Barat. Saran agar ditingkatkannya penyuluhan dan juga faktor risikonya seperti jarak kelahiran yang terlalu rapat. Kata Kunci : Faktor, gizi kurang balita